2012
DOI: 10.1111/j.1750-3841.2012.02949.x
|View full text |Cite
|
Sign up to set email alerts
|

Study on Mitigation of Acrylamide Formation in Cookies by 5 Antioxidants

Abstract: There is an urgent need for reducing the level of acrylamide produced during food processing. This study found that certain antioxidants (antioxidant of bamboo leaves and vitamin E) could effectively inhibit acrylamide formation in cookie processing without affecting sensory properties. The results suggested that the application of antioxidants could be an effective method to decrease acrylamide formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 40 publications
2
18
0
2
Order By: Relevance
“…Figure 8a shows that donut color decreases non-linearly as the level of vitamin B 3 is increased. Li et al [36] reported that cookies enriched with 0.2 g kg −1 bamboo leaf antioxidants and 0.1 g kg −1 vitamin E showed similar sensory attributes (taste, color, and texture) compared to the control cookie.…”
Section: Sensory Attributesmentioning
confidence: 99%
“…Figure 8a shows that donut color decreases non-linearly as the level of vitamin B 3 is increased. Li et al [36] reported that cookies enriched with 0.2 g kg −1 bamboo leaf antioxidants and 0.1 g kg −1 vitamin E showed similar sensory attributes (taste, color, and texture) compared to the control cookie.…”
Section: Sensory Attributesmentioning
confidence: 99%
“…However, the application has been severely limited due to the low solubility in the fatty phase. So far, AOB was proven to effectively mitigate the potential risk of acrylamide in potato crisps and French fries [91], fried chicken wings [94], cookies [52], and oriental fried bread sticks [96]. Rosemary extract presented its potential for inhibiting acrylamide and stabilizing the oil [84].…”
Section: Conclusion and Outlooksmentioning
confidence: 99%
“…The formation of AA in various foods might not be the same style due to their different components and heat treatment. Several researches focused on AA in cookies have been reported (Arribas‐Lorenzo and others ; Isleroglu and others ; Li and others ). However, the researches on AGEs in cookies are very limited.…”
Section: Introductionmentioning
confidence: 99%